AMAP Assessment 2013: Arctic Ocean Acidification - Arctic Monitoring and Assessment Programme (Arctic Monitoring and Assessment Programme, 2013)
Report documenting the findings and recommendations of the first comprehensive assessment of Arctic Ocean acidification (AOA) conducted by the Arctic Monitoring and Assessment Programme (AMAP). It is organized into five major sections: Introduction (background information), Acidification in the Arctic Ocean, Biological responses to ocean acidification, Portential economic and social impacts of ocean acidification on Arctic fisheries, and Conclusions and further work. It also includes references and a glossary.